Virginia Woolf’s “Modern Fiction”: A Paradigm Shift in Literary Criticism - Sharma, Mishail (Journal of Advanced Research in Humanities and Social Sciences; Vol 10 No 3 (2023): Journal of Advanced Research in Humanities and Social Sciences, 2023)
Virginia Woolf, a prominent figure in the modernist movement, was renowned for her avant-garde writing style and feminist perspectives. Woolf’s writing style explores the intricacies of human consciousness and the impermanence of time. Her writing frequently conveys how subjective and transient perception is, mirroring the fractured realities of the modern world. As a significant member of the Bloomsbury Group, an association of 20th century thinkers and artists, Woolf experimented with newer ideas that questioned conventional norm and embraced a freer, more liberated understanding. Her works, Mrs. Dalloway (1925), To the Lighthouse (1927), and Orlando (1928), demonstrate her skill of capturing the subtleties of identity, the passage of time, and the complexities of interpersonal relationships. In addition to her literary works, Woolf also authored a large number of literary articles and donned the role of a literary critic of her time. In her essay, “Modern Fiction” (first published in 1919), Woolf presents a radical critique of the traditional novel, calling for a shift towards a more experimental and thoughtful form of storytelling. She advocates for a more eloquent and subjective style of writing that conveys the complexity of the human condition in its raw state. Woolf, in her work, delineates the significance of portraying people’s inner thoughts and consciousness. This essay explores these key arguments put forth by Woolf in “Modern Fiction” (1919) and examines their impact on the literary world.